Morphometric Comparison Horned Beetle (Oryctes rhinoceros L.) from Location SEAT Ungaran, Banyumas, and Pangandaran - Achmad Himawan; Agus Prijono; Refdika Farid Pradana (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
The rhinoceros beetle (Oryctes rhinoceros L.) is a major pest of coconut and oil palm in Indonesia. Its attacks can cause up to 25% damage to young palms and reduce fresh fruit bunch production by up to 69%. This study aimed to compare the body morphometrics of male and female O. rhinoceros collected from SEAT Ungaran (oil palm), Banyumas (coconut), and Pangandaran (coconut) in Java. Adult beetles were obtained using pheromone traps (SEAT Ungaran) and manual collection (Banyumas and Pangandaran), then measured for 20 external characters, including body, pronotum, elytra, antennae, scutellum, and leg segments. Morphometric data were analyzed using t-tests to compare sexes within locations and analysis of variance, followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level to compare populations among locations. Several characters, particularly horn length, pronotum size, and hind leg segments, differed significantly between males and females at each site. In addition, body length, pronotum width, elytra length, and hind leg tibia length showed significant differences among populations from SEAT Ungaran, Banyumas, and Pangandaran. These characters are informative for distinguishing local populations of O. rhinoceros and provide baseline morphometric data to support location-specific management strategies for this pest.